Blended Learning Model in Technical Competence Training for Supervisors in the City of Bandung - Riyantini Riyantini; Ihat Hatimah; Mustofa Kamil; Jajat Sudrajat Ardiwinata; Cucu Sukmana (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2022)
This research aims to describe the blended learning model in technical competency training for supervisory functional positions in the city of Bandung. In this research apply analytical descriptive method and quantitative approach by using documentary study. The data collection instrument used was a questionnaire with 60 surveyors in Bandung as respondents. Data analysis techniques were data collection, presentation and conclusion. In the application of this model, training in the professional ability of the supervisory function of the city of Bandung was carried out which is expected to increase the level of quality of the inspector in practice. Things that need to be prepared before carrying out training with the Blended Learning method include preparing facilitators who understand information and communication technology, providing learning management systems (LMS), providing internet devices, digital libraries, and facilitating understanding by changing delivery materials. In organizing the training, the organizers must pay attention to matters relating to communication, logistics, operators, participants, infrastructure, evaluation and monitoring of other training materials. It is important to evaluate and monitor the training process to uncover various gaps, weaknesses and strengths, both in its implementation and in the process. The results of this training assessment indicated that there was an increase in differences in knowledge aspects between before and after the Blended Learning model training in technical skills training for supervisory functional positions in the city of Bandung.